Sustainable Certification Implementation and Its Economic Value in Gayo Coffee Farming - Alja Yusnadi; Rachmat Pambudy; Bayu Krisnamurthi; Etriya Etriya (Institut Pertanian Bogor, 2026)
Improving farmers' entrepreneurial orientation and strengthening informal social networks are crucial for increasing the adoption rate of certification schemes in the future. Simultaneously, targeted interventions for older and higher-income farmers are necessary to address the specific barriers to adoption. Furthermore, certification programs must be carefully evaluated to ensure maximum economic and environmental benefits. This study aims to examine the determinants of sustainable certification adoption in Gayo coffee farming and its economic value. A sample of 305 Gayo coffee farmers was analyzed using logistic regression and an economic value assessment. The findings indicate that age and participation in cooperatives negatively affect certification adoption, whereas income, number of employees, land size, total production, and engagement with informal communities have positive and significant effects. From an economic perspective, certified farmers perform better in terms of production, income, and profit and demonstrate a higher willingness to invest in inputs and labor, suggesting that certification contributes to improved farm efficiency despite higher production costs. However, the presence of high-performing non-certified farmers indicates that certification is not the only pathway to success in this field. This study provides new empirical evidence on how sustainable certification influences the economic performance of coffee farmers, highlighting its important role in promoting inclusive and sustainable rural development in Colombia. Moreover, these results imply that public policy should design targeted support mechanisms, such as training subsidies, extension services, and financial incentives. Keywords: Economic value, gayo coffee, green entrepreneurial, sustainable certification